Pengaruh Penggunaan Chatbot Artificial Intelligence Terhadap Kemampuan Berpikir Kritis Siswa Dalam Proses Pembelajaran Ekonomi : The Effect of Artificial Intelligence Chatbot Usage on Students' Critical Thinking Skills in the Economics Learning Proc - Ghafirin, Muhammad Azka; Hermawan, Yoni; Sadiah, Ati (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2025)
This research aims to determine the effect of AI chatbot usage on the critical thinking skills of eleventh-grade students at State Senior High School 6 Tasikmalaya. This study employed a quantitative method with a survey design. The population consisted of all 118 eleventh-grade students, using a saturated sampling technique. The research instruments included a Likert scale questionnaire for the AI chatbot usage variable and an essay test for the critical thinking skills variable. Data were analyzed using simple linear regression with the aid of SPSS 25. The results showed a significant effect of AI chatbot usage on students' critical thinking skills, with a calculated F-value of 122.268 > F-table of 3.92 and a significance of 0.000 < 0.05. The calculation of the Interval Tier Value (NJI) indicated that students' critical thinking skills were in the high category with a total score of 8,846. The highest indicator was 'simple explanation' (21.32%), while the lowest was 'further explanation' (17.17%). In conclusion, the use of AI chatbots positively contributes to the enhancement of students' critical thinking skills in economics learning.